Revolution in Eastern Europe : understanding the collapse of communism in Poland, Hungary, East Germany, Czechoslovakia, Romania, and the Soviet Union - Cipkowski, Peter (New York : Wiley, 1991)
Analyzes the fall of communism in Eastern Europe, country by country, during 1989 and 1990. Includes photographs, time lines, maps, and cartoons.
"Our changing world series"--Jacket.
Includes bibliographical references (p. [177]-179) and index.
HU OSA 300 - RFE/RL collection
Keywords: Europe, Eastern -- Politics and government -- 1989-